The efforts of Malaysian Muslim NGOs in spreading the message of peace in Malaysia: Activities and challenges - Ahmad H.Osman, Rahmah (Depart. IRKHS, International Islamic University Malaysia, 2017)
This paper investigates the efforts of Malaysian Muslim NGOs in spreading peace at our current time, a time of hyper-volatility exacerbated by the threats of extremism. Part one introduces briefly the pressing urgency of combating terrorism in our time, and stresses how the Malaysian context on terrorism should not be equated with other contexts. The second part of the paper discusses the importance of breaking the monopoly on religion that terrorist sympathisers take advantage of. The endeavours of the NGOs in dawah will be examined. Part three outlines the unique narrative on Islam that has been historically dominant in Malaysia and how this helps in forming a counter-narrative. Part four analyses how Malaysian NGOs deal with the malaise of identity crisis among Muslims. Part five looks into how NGOs in Malaysia widen the scope of Islam, thus allowing them to show via social projects a holistic vision of Islam as opposed to a reductive vision that terrorists endorse. The sixth part points to how the NGOs use creative strategies in spreading the peaceful message of Islam. Part seven highlights some challenges that Malaysian NGOs face in their pursuit of spreading a peaceful vision of Islam. The paper concludes that the success of Malaysian Muslim NGOs in spreading peace has been due to correctly understanding the threat of extremism, and also due to finding effective alternatives to extremism, thus allowing the NGOs to create a culture of peace in Malaysian society.